(untitled) (Canadian Medical Education Journal, 2025)
Our novel anatomy and ultrasound curriculum, integrating cadaver lab sessions and ultrasound workshops, enhances resident knowledge, confidence, and competence with ultrasound-guided procedures. Physiatry educators can adopt this longitudinal approach, incorporating spaced repetition and peer learning, to improve ultrasound training. Implementing this curriculum may lead to increased proficiency in ultrasound-guided procedures among residents. For programs without access to a cadaver lab, the curriculum can be modified by using available anatomical models or online cadaveric dissection videos. The minimum resources for programs wishing to implement a similar curriculum include an ultrasound machine and a faculty member for instruction.